Barriers and enablers of uptake and adherence to digital health interventions in older patients with cancer: A systematic review. Issue 8 (November 2022) - Hasnan, Syarafina; Aggarwal, Samuel; Mohammadi, Leila; Koczwara, Bogda
Abstract: Introduction: Digital health interventions (DHIs) provide patients with remote access to healthcare information and services through devices and online portals. Older patients (≥65 years old) with cancer may face difficulties using DHIs due to higher physical and psychological burden, but little is known about their pattern of use. The aim of this systematic review was to synthesise current findings related to user's perception of barriers and enablers to uptake and adherence of DHIs in this population. Materials and Methods: A search for English-language primary qualitative and mixed methods studies on uptake and adherence of DHIs among older patients with cancer was conducted on seven databases (CINAHL, Cochrane, Emcare, JBI, MEDLINE, Proquest, and SCOPUS), since inception until September 2021. Relevant data was extracted, appraised using the MMAT tool, and synthesised based on common themes. Results: Five studies met the eligibility criteria. All five studies examined barriers and enablers to uptake of DHIs but only two studies examined barriers and enablers to adherence to these interventions. Two themes – usability and perceived usefulness – emerged from all analyses. Usability was measured using system usability scale, ease of use survey, and observation or participant feedback. High usability to uptake was facilitated by minimalist and age-appropriate design. High usability to adherence was facilitated by customisability of DHIs and availability to provide feedback on DHI design. High perceived usefulness to uptake was facilitated by DHIs' ability to provide health information and to connect the patient to their healthcare team. High perceived usefulness to adherence was facilitated by DHIs ability to provide, reminders and contingency plans, reinforce long-term treatment plans, and keep healthcare teams updated on patients' progress. The review was limited by a small number of primary studies and longitudinal studies. Discussion: The enablers and barriers to uptake and adherence of DHIs among older patients with cancer followed the same themes (usability and perceived usefulness) found in other populations. The components of usability and perceived usefulness were similar to other populations, rendering the need for more studies to identify factors unique to this population.